Emerging Raman Applications and Techniques in Biomedical and Pharmaceutical Fields - Matousek, Pavel; Morris, Michael D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The book presents the latest technological advances in Raman spectroscopy that are presently redrawing the landscape of many fields of biomedical and pharmaceutical R&D. Numerous examples are given to illustrate the application of the new methods and compared with established and related techniques. The book is suitable for both new researchers and practitioners in this area as well as for those familiar with the Raman technique but seeking to keep abreast of the latest dramatic advances in this field.
Lasers, Spectrographs, and Detectors -- Fiber-Optic Raman Probes for Biomedical and Pharmaceutical Applications -- Characterisation of Deep Layers of Tissue and Powders: Spatially Offset Raman and Transmission Raman Spectroscopy -- Applications of Raman and Surface-Enhanced Raman Scattering to the Analysis of Eukaryotic Samples -- Raman Imaging and Raman Mapping -- Coherent Raman Scattering Microscopy -- Raman Optical Activity of Biological Molecules -- Chemometric Methods for Biomedical Raman Spectroscopy and Imaging -- Discovery and Formulation -- Raman Spectroscopy: A Strategic Tool in the Process Analytical Technology Toolbox -- Emerging Dental Applications of Raman Spectroscopy -- Raman Spectroscopy of Ocular Tissue -- Raman Spectroscopy for Early Cancer Detection, Diagnosis and Elucidation of Disease-Specific Biochemical Changes -- Raman Spectroscopy of Bone and Cartilage -- Raman Microscopy and Imaging: Applications to Skin Pharmacology and Wound Healing -- Raman Spectroscopy of Blood and Urine Specimens -- Quantitative Raman Spectroscopy of Biomaterials for Arthroplastic Applications -- Raman Spectroscopy: A Tool for Tissue Engineering -- Applications of Raman Spectroscopy to Virology and Microbial Analysis.
Keywords: Physics; Physics; Physics, general